Cytogenetic investigation of workers professionally exposed to phosphates and their derivatives - Glouib, K; Verschaeve, L; Naber, N; Hilali, A (Folia biologica, 2005)
The phosphor industry in Morocco employs a great number of workers that may be exposed to this essential but also toxic compound. In the present investigation, professionally exposed subjects from two different production lines (miners and production unit workers) were investigated for the presence of genetic damage in their peripheral blood lymphocytes. This was done with the well-known micronucleus assay. The proliferation and mitotic indices were also investigated. It was found that the micronucleus frequency was considerably increased compared to the frequency in non-exposed control subjects. Mitotic and proliferation indices were not increased, at least not in a statistically significant way. At the time being this investigation should be considered as a preliminary study in which the influence of potential confounders cannot be adequately assessed. However, our results are non-equivocal and clearly indicate a potential health risk in these workers.
Keywords: fosfáty; Cytochalasin B; dospělí; Phosphates; Adult; lidé; Middle Aged; Humans; lidé středního věku; Micronucleus Tests; Occupational Exposure; pracovní expozice; cytochalasin B; Life Style; životní styl; mikrojaderné testy